Self-Reported Cancer Prevalence among Hispanics in the US: Results from the Hispanic Community Health Study/Study of Latinos. - Frank J Penedo; Betina Yanez; Sheila F Castañeda; Linda Gallo; Katy Wortman; Natalia Gouskova; Melissa Simon; William Arguelles; Maria Llabre; Lisa Sanchez-Johnsen; Carrie Brintz; Patricia Gonzalez; et al. (PLoS ONE, 2016)
Cancer has surpassed heart disease as the leading cause of death among Hispanics in the U.S., yet data on cancer prevalence and risk factors in Hispanics in regard to ancestry remain scarce. This study sought to describe (a) the prevalence of cancer among Hispanics from four major U.S. metropolitan areas, (b) cancer prevalence across Hispanic ancestry, and (c) identify correlates of self-reported cancer prevalence. Participants were 16,415 individuals from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL), who self-identified as Cuban, Dominican, Mexican, Puerto Rican, Central or South American. All data were collected at a single time point during the HCHS/SOL baseline clinic visit. The overall self-reported prevalence rate of cancer for the population was 4%. The rates varied by Hispanic ancestry group, with individuals of Cuban and Puerto Rican ancestry reporting the highest cancer prevalence. For the entire population, older age (OR = 1.47, p < .001, 95% CI, 1.26-1.71) and having health insurance (OR = 1.93, p < .001, 95% CI, 1.42-2.62) were all significantly associated with greater prevalence, whereas male sex was associated with lower prevalence (OR = 0.56, p < .01, 95% CI, .40-.79). Associations between study covariates and cancer prevalence also varied by Hispanic ancestry. Findings underscore the importance of sociodemographic factors and health insurance in relation to cancer prevalence for Hispanics and highlight variations in cancer prevalence across Hispanic ancestry groups. Characterizing differences in cancer prevalence rates and their correlates is critical to the development and implementation of effective prevention strategies across distinct Hispanic ancestry groups.